Computational study of T1 lipase activation and metallolipase engineering using modified T1 lipase as scaffold - Abdul Rahman, Mohd Zulhilmi (2013)
Biocatalysts play an important role in white biotechnology, but the features of the enzymes, such as the thermal stability, pH optimum, and the need for a co-factor for catalytic activity may not be compatible with the industrial processes. Screening of biocatalysts that can withstand harsh industrial processes is time consuming and may not readily available in nature. Through protein engineering, enzyme with desired characteristics could be designed and synthesized. However, in order to achieve such goals, detailed mechanism underlying the mode of action of the enzyme must be fully understood. The emergence of great interest in the field of biomimicry and synthetic biology in recent years, has led to a rapid development in the construction of artificial metalloenzyme. Artificial metalloenzyme which was claimed to be the chemical synthesis of the future is a combination of active organometallic moiety with a macromolecular host. In this study, the activation process of T1 lipase at the molecular level was investigated via computational approach and a functional artificial metalloenzyme was engineered as a novel metallolipase by using the modified scaffold of T1 lipase. Molecular Dynamics (MD) simulations of native T1 lipase in different solvent environments (water and water-octane interface) and temperatures (20˚C, 50˚C, 70˚C, 80˚C and 100˚C) were performed in order to investigate the enzyme activation process and the importance of the lid structure in activating the enzyme. Based on the structural analysis of the lipases in the family I.5, the lid domain was proposed to comprise α6 and α7 helices connected by a loop, thus forming a helix-loop-helix motif. Throughout the MD simulations experiments, lid displacements were only observed in the water-octane interface, not in the aqueous environment, and they were observed in respect to the temperature effect, suggesting that the activation process is governed by interfacial activation coupled with temperature switch activation. Examining the activation process in detail revealed that the large structural rearrangement of the lid domain was caused by the interaction between the hydrophobic residues of the lid with octane, a non-polar solvent, and this conformation was found to be thermodynamically favorable. These findings on T1 lipase activation process are very important and crucial as it will aid in the next step which is the redesigning of T1 lipase structure. In order to investigate the importance of the lid domain toward the behavior of lipase, four new constructs (D1, D2, D3, and D4) were successfully designed and engineered, conferring deletion or modification within the lid domain of T1 lipase. Among those constructs, the D4 lipase was chosen for enzyme characterization since it possessed a completely exposed active site while retaining the catalytic efficiency compared to other constructs. In order to study the effect on T1 lipase characteristics upon lid removal, D4 lipase was subjected to enzyme purification and characterization. The optimum temperature was shifted to a lower temperature (50˚C) and showed a higher preference toward substrate with a longer chain length. By utilizing the solvent exposed structure of D4 lipase as the protein scaffold, a new zinc binding site was engineered for the attachment of the metal ion that was used as the nucleophile in the catalysis replacing the existing catalytic Ser113. The newly engineered enzyme was identified to be catalytically active and able to hydrolyze p-nitrophenyl decanoate with a specific activity of 0.435 U/mg. Although the catalytic efficiency of the artificial metallolipase was less than the D4 lipase, the catalytic effiency can be further enhanced by employing directed evolution in the future study. Furthermore, D4 metallolipase was the only metallolipase reported so far.